An optimized fluorescent reporter enables rapid and cost-effective quantification of regulated secretion from neuroendocrine cells - Carter, Theodore; McTavish, Alice; Asensio, Cedric S. (Frontiers in Endocrinology, 2025)
The ability to quantify protein secretion is critical for studying the secretory pathway. This is particularly important in endocrine cells where dysregulated hormone secretion is associated with the development of diseases such as type 2 diabetes. To measure protein secretion, researchers have previously relied on techniques such as ELISA, RIA and Western blot, which all present limitations, including cost and time consumption. To address these challenges, we developed a plate reader-based assay using an optimized red fluorescent reporter, NPY-sfCherry3c. This reporter showed enhanced expression, proper sorting into secretory granules, and robust secretion from both INS-1 832/13 and PC12 cells. As NPY-sfCherry3c displayed better signal-to-background ratio compared to previously published reporters (e.g. NPY-GFP, NPY-mCherry), secretion could easily be detected within a few minutes of stimulation, demonstrating the assay’s enhanced sensitivity. Our results suggest that NPY-sfCherry3c is a valuable tool to perform rapid and cost-effective secretion assays from neuroendocrine cells.